Exploring the Contribution of Green Sukuk in Achieving Sustainable Development Goals (SDGs) (Case Study of Malaysia and Indonesia) - Ziarmal, Abdullah (El-Barka, 2025)
The purpose is this study is to illustrate green sukuk and analyze the role of green sukuk in achieving of sustainable development goals (SDGs) based on the relevant projects of Indonesia and Malaysia. The research methodology used for this study is descriptive based qualitative. Data has taken from the various sources such as annual reports, articles, books, websites and etc. Findings of this study indicates that green sukuk markets in both Malaysia and Indonesia are the symbols of huge commitment to the governments of Malaysia and Indonesia in term of contribution and getting close to the targets to the sustainability specified and selected by United Nations an agenda until 2030. Various projects such, renewable energy, waste management, reducing disasters and floods risks, low carbon transport, sustainable cities have been funding through green sukuk in both Malaysia, and Indonesia. This study results also indicates that in the global market of green sukuk Indonesia is ranking toped with the 2/5 of market cap. On the other hand, Malaysia is leading in green sukuk issuance based on owing 57% of issuers in the market. In term of practical implication, this study will be a roadmap for the next people who wants to illustrate the role of green sukuk in their respective countries. Furthermore, this will be a meaningful study for the researchers of those countries that lack green financing such as Afghanistan and others, they will be use this article as a guide article during conducting their own. This study can also help public regarding transferring the concept and theory of sukuk, green sukuk, and SDGs. Top of Form